Croatian Regional Strategy in the Framework of the EU Accession Process - Zlatan Frohlich (European Regional Science Association (ERSA), 2006)
A limitation on the implementation of modern regional policy in Croatia is the inherited doctrine of the reconstruction of war affected areas. This doctrine is no longer appropriate to the needs of new regional policy, which must be formulated in the context of EU accession. This is especially important considering that the EU emphasizes that member states must be in a position to withstand competitive pressures in the single market as a key condition for accession. In this context, regional policy will be closely tied into the accession strategy. A major objective will be to prepare for the introduction of EU cohesion policy and the Structural Funds. The pre-accession funds will contribute to that effort. The situation in Croatia today is that while "balanced regional development" is one of seven key government priorities, there is no clear definition of what this means. There is a fragmented listing of regions deemed to have special problems without, on the face of it, any coherent profile of those development needs. The National Strategy for Regional Development will seek to address these issues. The implications, therefore, for approach to the analysis of regional policy in Croatia today is that we concentrate essentially upon three main fields of enquiry from two perspectives – top-down and bottom-up. These are: Assessment of the overall policy framework for regional development, including the current legal framework in particular policies, legal acts and regulations which affect the development of those parts of the country which can be loosely termed "assisted areas". Assessment of the institutional and administrative capacity in place. Appraisal of the types of regional development instruments currently deployed and their effectiveness in dealing with development needs at national, regional and local level. The strategy sets the context for balanced regional development both at national and sub-national level as well as draws attention to development needs of the 'assisted areas' as well as counties highlighting their different development profiles. It brings together the main analytical parts – policy framework, institutional context and finally an assessment of the existing development interventions. This is followed by a SWOT analysis before moving to a set of conclusions and next steps which will frame the strategic rationale behind the strategy. The paper is linked to the project Strategy and Capacity Building for Regional Development (CARDS 2002 Programme for Croatia): Analysis Section for Strategy.
Keywords: 330